Internet Use and Fertility Behavior among Reproductive-Age Women in China - Peng Nie; Xu Peng; Tianyuan Luo (Institute of Labor Economics (IZA), 2022)
Using longitudinal data from the 2014\~Aâ,¬â exteuroœ2018 China Family Panel Studies, we investigate the impact of internet use (IU) on fertility among reproductive-age women. We find that IU reduces the number of children born, with more pronounced effects among those with a moderate level of education, those aged 16\~Aâ,¬â exteuroœ19, rural residents, and those who are married. These results are robust to alternative IU measures and a series of estimation approaches that control for endogeneity. IU participation affects the number of children born through decreased marital satisfaction, changed attitudes toward traditional gender roles, a reduction in the importance placed on ancestral lines, deteriorated health and reduced fertility preferences.
Keywords: D13; D91; J13; J16; R20; 330; fertility; internet use; reproductive-age women; China